2018
DOI: 10.1111/cdoe.12366
|View full text |Cite
|
Sign up to set email alerts
|

Identification of caries risk in 2‐year‐olds

Abstract: A small proportion of 2-year-olds had caries, but these children had several decayed teeth. Substantial differences in oral health and oral health behaviour were found between Western and non-Western children. The preventive care delivered to the studied children failed to prevent caries increment from 2 to 5 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…The timing seems to be of importance and it is suggested that tooth brushing should be commenced not later than at 1 year-of age (Kumar et al 2016). The best evidence comes from randomized controlled trials and from prospective observational studies; recent data from a Norwegian birth cohort have confirmed the importance of an early start and twice daily brushing with fluoride toothpaste to reduce the development of dental caries from 2 to 5 years of age Wang 2015, 2017;Wigen et al 2018). We have previously described the influence of birth-related and family factors on early childhood caries development up to the age of 5 years in a birth cohort that was monitored prospectively (Boustedt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The timing seems to be of importance and it is suggested that tooth brushing should be commenced not later than at 1 year-of age (Kumar et al 2016). The best evidence comes from randomized controlled trials and from prospective observational studies; recent data from a Norwegian birth cohort have confirmed the importance of an early start and twice daily brushing with fluoride toothpaste to reduce the development of dental caries from 2 to 5 years of age Wang 2015, 2017;Wigen et al 2018). We have previously described the influence of birth-related and family factors on early childhood caries development up to the age of 5 years in a birth cohort that was monitored prospectively (Boustedt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…habits necessary to prevent caries development in newly erupted permanent teeth. One study has shown that children who develop caries before 2 years of age had more caries at 5 years of age than children without caries at age 2 years [26]. The results from this study suggest that children who develop caries soon after the eruption of primary teeth have increased caries risk also in the young permanent dentition.…”
Section: Discussionmentioning
confidence: 47%
“…Initiation of favourable oral health habits should preferably start when the first primary tooth erupts. In Norway, collaboration between general health services and dental services is established [26,27]. New national guidelines regarding oral care in children younger than 3 years of age were introduced in 2019 [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, prior work has not supported an association between fluoride exposure and pediatric neurodevelopment. 9,10 Our findings, as they relate to tertiary oral health services, are unexpected, because the development of S-ECC in the US is largely thought to be driven by oral health behaviors, such as preventive dental care, regular toothbrushing, or reducing intake of sugary foods and beverages, [39][40][41][42] The lack of an association between CWF and PQIs suggests that an association between CWF and DGA is unlikely to be related to unobserved local area factors.…”
Section: Discussionmentioning
confidence: 99%